2012
DOI: 10.1186/1472-6882-12-89
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpene lactones isolated from indigenous Middle Eastern plants inhibit tumor promoter-induced transformation of JB6 cells

Abstract: BackgroundSesquiterpene lactones (SL) are plant secondary metabolites that are known for their anti-fungal, anti-bacterial, anti-inflammatory, and anti-tumor properties. Considering that several SL-derived drugs are currently in cancer clinical trials, we have tested two SL molecules, 3-β-methoxy-iso-seco-tanapartholide (β-tan) isolated from Achillea falcata and salograviolide A (Sal A) isolated from Centaurea ainetensis, for their anti-tumor properties. We used the mouse epidermal JB6P + cells as a model for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 47 publications
1
16
1
Order By: Relevance
“…The neoplasm was formed at about day 15 after prolonged Wnt10b induction, which is in similar duration to JB6P+ cell transformation under ectopic stimuli (Su et al 2014). While different from JB6P+ cell clustering induced by TPA, EGF, or TNF-a signaling, which showed simple cell aggregation in previous studies (Saikali et al 2012; Han et al 2011; Su et al 2014), the colonies observed in the present study were totally newly induced. Also, the cell colony displayed obvious boarder to the surrounding cells, which were not transformed.…”
Section: Discussioncontrasting
confidence: 95%
“…The neoplasm was formed at about day 15 after prolonged Wnt10b induction, which is in similar duration to JB6P+ cell transformation under ectopic stimuli (Su et al 2014). While different from JB6P+ cell clustering induced by TPA, EGF, or TNF-a signaling, which showed simple cell aggregation in previous studies (Saikali et al 2012; Han et al 2011; Su et al 2014), the colonies observed in the present study were totally newly induced. Also, the cell colony displayed obvious boarder to the surrounding cells, which were not transformed.…”
Section: Discussioncontrasting
confidence: 95%
“…Conversely, several reports indicate that UA remarkably reduces oxidative stress and increases the activity of antioxidant enzymes [49-51]. We observed that the expression of HO-1 (antioxidant), NQO1, and UGT1A1 (detoxification) noticeably increased at both the mRNA and protein levels in the JB6 P+ cells treated with UA; however, TPA activated AP-1, NF-κB, and ERK 1/2 as well [43, 52]. Moreover, UA targets AP-1, NF-κB, and ERK 1/2 [2].…”
Section: Discussionmentioning
confidence: 64%
“…On CaCo2, the IC50 of I. vis was 12µg/ml in the Trypan blue assay and 22µg/ml by the MTT test, indicating high potency. Since the IC50 of the extracts were less than 30µg/ml, this coincides with the American National Cancer Institute, which specified definite criteria for cytotoxic activity of plant extracts at IC50 less than 30 µg/ml [22]. Insignificant differences were observed among the two studied plants for each of the cells that were evaluated, which indicates comparable potencies.…”
Section: Comparative Antiproliferative Activity Of I Vul Versus I Vmentioning
confidence: 93%